Using cytochrome P4501A1 expression in liver and blubber to understand effects of persistent organic pollutant exposure in stranded Pacific Island cetaceans. (22nd June 2015) - Bachman, Melannie J.; Foltz, Kerry M.; Lynch, Jennifer M.; West, Kristi L.; Jensen, Brenda A.
Abstract Elevated levels of persistent organic pollutants (POPs) have been reported in tropical Pacific Island cetaceans and their environment. In addition, recent health concerns in cetacean populations have warranted investigation into potential physiological effects from POP exposure for this region. Cytochrome P450 1A1 (CYP1A1) is a candidate for examining such effects. This well‐studied biomarker of exposure and effect was examined in stranded cetacean liver using immunoblot (n = 39, 16 species) and blubber using immunohistochemistry (n = 23, 10 species). Paired tissue samples allowed for CYP1A1 comparisons not only between species but also within each individual animal to examine differences between tissue types. Liver CYP1A1 expression correlated positively and significantly with blubber concentrations of all POP categories (n = 39, p < 0.050) except octachlorostyrene and pentachlorobenzene (p > 0.100). Among Stenella species, liver CYP1A1 tissue expression was correlated negatively with the sum of all blubber layer endothelial cell CYP1A1 expression (n = 14, p = 0.049). Overall, elevated expression of liver CYP1A1 confirms its use as a biomarker of POP exposure to cetaceans stranded in the tropical Pacific basin. Environ Toxicol Chem 2015;34:1989–1995. © 2015 SETAC